PJMHS 2022
DOI: 10.53350/pjmhs20221611235
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study between Milligan Morgan Versus Ligasure Haemorrhoidectomy

Abstract: Purpose of Study: To compare the short term outcome of Ligasure haemorrhoidectomy with Milligan Morgan technique for third and fourth degree haemorrhoids. Design of Study: The present study was a single-blind randomized controlled trial. Duration and Location of Study: This trial was conducted at Akhtar Saeed Trust Teaching Hospital, Lahore. Duration of study is 6 months June 2021 to December 2021. Patients and Methods: A total of 80 subjects suffering from 3rd or 4th degree haemorrhoids were enrolled in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…On the other hand, Aljabery RMS et al 13 , reported the mean age of their subjects was 38.9 years, with they also found males in majority 66.66% and females 33.44%. Another study by Baig AA et al 14 reported that the average age of their subjects was 41.54±6.380 years, with males being the most common at 61.3% and females at 38.7%. Although the exact cause of male predominance in hemorrhoids is not well understood, lifestyle factors like diet, obesity, and lack of physical activity may play a role, and occupational hazards like long periods of sitting or heavy lifting may also contribute to the development of hemorrhoids.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, Aljabery RMS et al 13 , reported the mean age of their subjects was 38.9 years, with they also found males in majority 66.66% and females 33.44%. Another study by Baig AA et al 14 reported that the average age of their subjects was 41.54±6.380 years, with males being the most common at 61.3% and females at 38.7%. Although the exact cause of male predominance in hemorrhoids is not well understood, lifestyle factors like diet, obesity, and lack of physical activity may play a role, and occupational hazards like long periods of sitting or heavy lifting may also contribute to the development of hemorrhoids.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown to be effective in reducing anal spasms and pain after hemorrhoidectomy [ 4 ]. In addition, It has been associated with significantly less surgical time and bleeding compared to traditional hemorrhoidectomy [ 5 ].…”
Section: Introductionmentioning
confidence: 99%